Is intuition really cooperative? Improved tests support the social heuristics hypothesis - Isler, Ozan; Maule, John; Starmer, Chris (Public Library of Science, 2018)
Understanding human cooperation is a major scientific challenge. While cooperation is typically explained with reference to individual preferences, a recent cognitive process view hypothesized that cooperation is regulated by socially acquired heuristics. Evidence for the social heuristics hypothesis rests on experiments showing that time-pressure promotes cooperation, a result that can be interpreted as demonstrating that intuition promotes cooperation. This interpretation, however, is highly contested because of two potential confounds. First, in pivotal studies compliance with time-limits is low and, crucially, evidence shows intuitive cooperation only when noncompliant participants are excluded. The inconsistency of test results has led to the currently unresolved controversy regarding whether or not noncompliant subjects should be included in the analysis. Second, many studies show high levels of social dilemma misunderstanding, leading to speculation that asymmetries in understanding might explain patterns that are otherwise interpreted as intuitive cooperation. We present evidence from an experiment that employs an improved time-pressure protocol with new features designed to induce high levels of compliance and clear tests of understanding. Our study resolves the noncompliance issue, shows that misunderstanding does not confound tests of intuitive cooperation, and provides the first independent experimental evidence for intuitive cooperation in a social dilemma using time-pressure.